2003
DOI: 10.1007/s00467-003-1109-1
|View full text |Cite
|
Sign up to set email alerts
|

Acute pyelonephritis and sequelae of renal scar in pediatric first febrile urinary tract infection

Abstract: To investigate the incidence of acute pyelonephritis (APN) and renal scarring in children with febrile urinary tract infection (UTI), 191 of 216 (88%) children with their first episode of UTI received 99m Tc-dimercaptosuccinic acid renal single-photon emission computed tomography. They were investigated within 7 days of admission and were followed for 6 months. One hundred and six patients (49.1%) underwent a voiding cystourethrogram. The incidence of vesicoureteric reflux (VUR) in group I (≤1 year old) was 22… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
3
12

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(50 citation statements)
references
References 25 publications
(19 reference statements)
2
33
3
12
Order By: Relevance
“…Adult pig kidneys scar as quickly as those of piglets with VUR and UTI 25 and scarring is known to occur in adult mature kidneys transplanted into pediatric patients 26 . Some recent studies have reported that the age may not be a risk factor for renal scarring and the risk in older children is the same 21, 27, 28 or even higher 29, 30 as compared to the younger children.…”
Section: Risk Factors For Rnmentioning
confidence: 99%
“…Adult pig kidneys scar as quickly as those of piglets with VUR and UTI 25 and scarring is known to occur in adult mature kidneys transplanted into pediatric patients 26 . Some recent studies have reported that the age may not be a risk factor for renal scarring and the risk in older children is the same 21, 27, 28 or even higher 29, 30 as compared to the younger children.…”
Section: Risk Factors For Rnmentioning
confidence: 99%
“…Upper UTIs in young children can cause permanent kidney damage. An estimated 57% of children with acute pyelonephritis develop renal scarring [5]. UTIs are classically treated with trimethoprim/sulfamethoxazole or ciprofloxacin to eradicate the infecting strain.…”
Section: Introductionmentioning
confidence: 99%
“…DMSA scintigraphy is considered the most sensitive test for the diagnosis of renal involvement and the subsequent development of renal scarring [1, 2]. The renal cortical changes are acceptably detected by Tc-99m-DMSA renal scintigraphy.…”
Section: Discussionmentioning
confidence: 99%
“…Technetium-99m-dimercaptosuccinic acid (DMSA) renal scintigraphy is considered the most sensitive test for the diagnosis of renal involvement and the subsequent development of renal scarring [1, 2]. …”
Section: Introductionmentioning
confidence: 99%